A Micro-class Teaching Data Retrieval Method of Business English Based on Network Information Classification (Informatica, 2024)
In order to quickly extract the required micro-class teaching data of business English in the fragmented network information environment, a micro-class teaching data retrieval method of business English based on network information classification is offered. This way, it constructs a network information classification method on the basis of the optimised SVM model, and the parameters of the SVM model are optimised and trained by the improved artificial bee colony algorithm. After optimising the function of the SVM method, the method classifies the online teaching information of various business English micro-class teaching; In the classified network information set, the targeted retrieval method of network teaching resources according to big data technology is adopted to obtain the teaching data with the highest similarity to the user's retrieval data by clustering and complete the targeted retrieval of micro-class teaching data. The experimental results show that the retrieval delay of the proposed method for micro-class teaching data retrieval of business English is less than 1s, the number of correct retrievals is relatively high, and there are few wrong retrieval phenomena.